Multigene analysis of Leucoma wiltshirei Collenette, 1938 using combined mitochondrial and nuclear DNA sequences (Lepidoptera: Erebidae) - Hosseini-Chegeni, Asadollah; Tavakoli, Majid (SHILAP Revista de lepidopterología, 2025)
The study focuses on molecular identification of Leucoma wiltshirei Collenette, 1938, a significant pest in Iranian oak stands. It employs DNA sequencing of mitochondrial and nuclear gene fragments for accurate identification. The 12S rRNA gene region is highlighted for its suitability in identifying Leucoma Hübner, [1822] species. The analysis revealed genetic characteristics and diversity within the Leucoma wiltshirei gene fragments, contributing valuable information for species identification and understanding their evolutionary relationships.